TINJAUAN YURIDIS TERHADAP SANKSI PIDANA KEBIRI DALAM PERKARA TINDAK PIDANA PEDOFILIA - Rudi Hartono; Erdianto '; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The rise of sexual violence in children or the so-called pedophilia into a picture of how weak security guarantees. This prompted the birth of Perpu No. 1 of 2016 which regulates the Punishment of the Kiri as a new punishment for pedophiles. Until now still reap the pros or cons or still in debate. The Punishment of the Left raises the debate over whether sanctions of the left can provide protection and prevention associated with cultural human rights adopted in Indonesia. Human rights embraced in Indonesia are not liberal human rights as they are adopted in western countries, especially those that enforce the law. Human rights in Indonesia is a human right that embraces the principles of Pancasila. If it is linked to Article 10, Article 33, Article 71 and Article 74 of Law 39/1999 on Human Rights, this is contradictory, because the Government should respect and uphold Human Rights for the sake of every survival person.The purpose of this thesis writing is: to know the Law Arrangement In Indonesia Against Pedophilia Crime Sanction, secondly, criminal sanction in the case of criminal pedophilia in the perspective of Human Rights in Indonesia. This type of research is normative legal research or can be called also research doctrinal law.From the research results of the problem there are two main points that are concluded, First, the laws and regulations that apply to crimes of sexual violence you value from the Criminal Code, Act No.23 of 2002 on Child Protection into Law No.35 of 2014 until the exit Perpu No. 1 Year 2016 which adds to the punishment of the hazel, still prioritizes penalties. Second, the prevailing criminal offense has been contradictory to the applicable Human Rights in particular the right to hereditary and the right not to be tortured. Punishment also has contradicted the principle of Prisons which prioritizes the self-improvement of the perpetrator to be accepted again in the midst of society.Kaywords: Criminal Sanctions Kebiri, Pedophilia Crime, Human Rights.